The Features Of Social Research Network For Facilitating Research Activities From Medical Sciences Researchers' Perspective - Zahra Batooli; Maryam Nazari (Tehran University of Medical Sciences, 2014)
Background and Aim: The importance of social networking sites (SNSs) is evident as a tool for research team working and for enabling researchers to share the results and experiences. The present study aims to identify the features of SRNs for facilitating research practices from the perspective of medical sciences researchers and to study the reasons why they use these networks.  Materials and Methods: This was a qualitative research that employed content analysis approach. The participants were 10 medical researchers who were active in ResearchGATE, and were selected through purposeful sampling. The selection criterion was their scores in ResearchGATE (RG). RG scores are allotted based on publications, questions, answers and followers.  The data were gathered using semi-structured interviews, and then were thematized and presented in the form of a list; the list of SRNs' most important features for the field of medical sciences.  Results: The findings of data analysis revealed eight features for SRN's: presenting themselves and identifying other researchers, communicating and collaborating with other researchers, sharing information, finding information, managing resources and citations, keeping the researcher up to date, rating, and setting the network.   Conclusion: Due to the importance and role of SRNs in communication and collaboration between researchers and their scientific production management, introduction of features identified in this study can enhance these SNSs' efficiency and effectiveness. Information science professionals can use the findings of this research to design educational workshops on "Familiarity with the features of SNSs for researchers" as a new information service in libraries.